METHODOLOGY FOR FORMING PERSONAL QUALITIES IN CHILDREN IN COOPERATION WITH PARENTS AND EDUCATORS (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the development of personal qualities in children through a collaborative methodology involving both parents and educators. The formation of such qualities—responsibility, empathy, self-confidence, discipline, and social awareness—is a fundamental task of early childhood education. While schools provide structured environments for learning, the family remains the child’s first and most influential institution of socialization.